A new approach for evaluating international EPC contractors in Iran's energy sector. Issue 7 (21st September 2020) - Bonyani, Abbas; Alimohammadlou, Moslem
Abstract: Ever since the sanctions on economic and financial cooperation with Iran have been lifted, leading EPC contractors in the field of energy have expressed their interest in Iran's energy sector. This study sought to formulate a model for assessing and ranking foreign EPC companies which are willing to cooperate with Iran. To accomplish this, the best-worst method was used. In this study, the required data were collected through a questionnaire that organized the opinions of 8 experts in the field of oil, gas and petrochemicals. Results the final assessment revealed that leading European and American companies, along with popular Korean companies, had higher ranks, compared to the others and those which cooperated with Iran during the sanctions.